Pengaruh Profitabilitas dan Likuiditas terhadap Pengungkapan Sustainability Report di Perusahaan yang Terdaftar pada Jakarta Islamic Index (JII) - Eko Setiawan; Yuliansyah Yuliansyah; Rindu Rika Gamayuni (Studi Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: The purpose of this study is to examine the effect of profitability and liquidity on our sustainability report. Previous research used financial performance variables with profitability, liquidity, leverage, and activity ratios in manufacturing companies in 2014 and Global Reporting Initiative (GRI) 2006 measurements with 79 triple bottom line items (disclosure of economic, social, and environmental performance). Method: Liquidity and profitability are the independent variables in this study. While the measurement variable is the 2016 Global Reporting Initiative (GRI) sustainability report, which is 91 items. The sample uses the Purposive Sampling method on companies listed on the Jakarta Islamic Index (JII) in 2018-2020. Based on the purposive sampling method, the number of companies that have disclosed sustainability reports is 18 companies that are sampled in this study. The analytical method used in this research is multiple regression analysis methods with SPSS 20 software. Results: The results show that profitability and liquidity have no effect on the Sustainability Report. It can be seen by testing the hypothesis that the profitability variable as measured by return on assets has a significance value of 0.160 > 0.05, while the liquidity variable as measured by the current ratio has a significance value of 0.072 > 0.05. Limitations: This study cannot be used as a basis for overall selection for companies listed in the Jakarta Islamic Index (JII), because the population in this study is limited to companies. consistently recorded in 2018-2020 and the variables in this study are still very small in scope to find out what factors influence the alleged Sustainability Report on companies listed on the Jakarta Islamic Index (JII). Contribution: Further research can be improved and improved in quality, it is hoped that the sample can be used for all companies listed on the Indonesia Stock Exchange.